The Effect of Carbohydrate Ingestion on Performance and Indices of Fatigue in Adolescent Soccer Players During a Simulated Game - Panagiotis G. Miliotis; Spyridoula D. Ntalapera; Dimitriοs C. Stergiopoulos; Athanasios C. Zavvos; Panagiota Klentrou; Ifigeneia Giannopoulou; Nickos D. Geladas (Sports)
We examined the effects of carbohydrate ingestion on endurance performance and fatigue during a soccer simulation in adolescent soccer players and evaluated the protocol’s reliability. Nine (13.5 ± 0.4 years pre-PHV) soccer players performed two soccer simulation intermittent exercise sessions on the treadmill (60 min) while consuming 4 boluses of either a CHO or PLC beverage in random, counterbalanced order. Before and immediately after each exercise session, MVC was measured for the quadriceps and the hand. Participants also performed a TTE on a cycle ergometer on three occasions, after each simulation exercise session (CHO and PLC), and on another day in a rested state (CON). The simulation protocol produced an ICC of 0.96 ([0.77–0.98 95%CI], p = 0.01) for VO2, with 2.24%CV between trials, suggesting strong reliability. TTE was higher (p = 0.01) in the CHO condition (123 ± 33 s) compared to PLC (85 ± 5 s) by 29%. The relative reduction in MVCLEG was more pronounced in the PLC (22 ± 11%) condition than in CHO (14 ± 6%) (p = 0.05). Compared to the PLC, CHO resulted in lower RPElocal during the second half of the simulation protocol (p < 0.05). Carbohydrate ingestion can improve endurance performance and reduce peripheral fatigue during a reliable soccer simulation that resembles the physiological demands of a youth soccer match.